Seasonal influenza vaccine (A/New York/39/2012) effectiveness against influenza A virus of health care workers in a long term care facility attached with the hospital, Japan, 2014/15: A cohort study. Issue 11 (November 2016) - Ishikane, Masahiro; Kamiya, Hajime; Kawabata, Kunio; Higashihara, Masahiko; Sugihara, Motohiro; Tabuchi, Ayako; Kuwabara, Masao; Yahata, Yuichiro; Yamagishi, Takuya; Odagiri, Takato; Sugiki, Yuko; Ohmagari, Norio; et al.
Abstract: The 2014/15 influenza season started earlier than usual, and intense activity was reflection of circulation of antigenically-drifted and vaccine-mismatched dominant A(H3N2) viruses. Although inpatients and health-care workers (HCWs) had a high influenza vaccination coverage rate well prior to the beginning of influenza season, numerous outbreaks of influenza A(H3N2) infection with fatal cases were reported in long-term care facilities (LTCFs) in Japan during 2014/15 influenza season. In January 2015, we were given opportunity to conduct outbreak investigation of influenza A at facility A (LTCF attached with hospital) in Western part of Japan. We evaluated overall and occupation-stratified influenza vaccine effectiveness (VE) among HCWs at facility A using a retrospective cohort design. Overall VE, occupation-stratified VE and adjusted VE (AVE) with 95% confidence intervals (CIs) were estimated using the following formula: (1-relative risks (RR) or 1-adjusted RR) × 100%. Overall vaccine coverage rate among HCWs was 85%. Overall VE for HCWs was 28% (95% CI: −70 to 67) and overall AVE was 3% (95% CI: −34 to 30). Although there was no severe cases, our results indicated that even with high vaccination coverage rate with appropriate vaccination timing, the VE was low for HCWs, which echoes with previously reported VE from other northern hemisphere countries. However, rehabilitation group who had high awareness against influenza as a group and carried out intensive precautions from early influenza season had no cases. We conclude that multiple preventive measures in addition to high vaccination rate is necessary for preventing influenza of HCWs working at LCTFs.